Composite structures, design, safety, and innovation - Backman, B. F. (Elsevier, 2005)
Aerospace structural design, especially for large aircraft, is an empirical pursuit dominated by rules of thumb and often-painful service experiences.Expertise on traditional materials is not transferable to "new materials, processes and structural concepts.This is because it is not based on or derived from well-defined measures of safety.